2019
DOI: 10.1111/jocd.13120
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about proper use of sunscreen in people of color: A Jordanian‐based survey

Abstract: Introduction The use of sunscreen is an important preventive measure against skin cancer and treatment for other skin conditions. There is evidence pointing to lack awareness and misconceptions regarding use of Sunscreen. This is especially evident in populations with skin of color (POC). Methods This is a cross‐sectional study of 2000 individuals. A structured questionnaire was designed to collect data on general knowledge and use of sunscreen as well as reasons for stopping use of sunscreen. Results The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 27 publications
5
27
2
Order By: Relevance
“…A study conducted in Lima, Peru, also found high rates of knowledge and use of photo-protectors among dermatology patients, with "78.9% of patients reporting that they knew about photo-protectors (sunscreens) and 52.3% reported that they used photo-protectors regularly". 23 Gender distinction was noted, with more women reporting sunscreen use, a finding that other studies have confirmed 1,16,[21][22][23][24] Traditional gender roles and societal norms greatly influence beliefs that impact sunscreen use. Women are typically the target audience of the skincare industry and are regular consumers of cosmeceutical products.…”
Section: Discussionmentioning
confidence: 73%
“…A study conducted in Lima, Peru, also found high rates of knowledge and use of photo-protectors among dermatology patients, with "78.9% of patients reporting that they knew about photo-protectors (sunscreens) and 52.3% reported that they used photo-protectors regularly". 23 Gender distinction was noted, with more women reporting sunscreen use, a finding that other studies have confirmed 1,16,[21][22][23][24] Traditional gender roles and societal norms greatly influence beliefs that impact sunscreen use. Women are typically the target audience of the skincare industry and are regular consumers of cosmeceutical products.…”
Section: Discussionmentioning
confidence: 73%
“…In our study, the most common reason behind not using sunscreen was the high cost followed by numerous side effects of these products. Alqarqaz et al 18 reported similar findings. Additionally, R.R.…”
Section: Discussionmentioning
confidence: 63%
“…On the contrary, skin allergies, irritation, whitening, and acne were the most reported disadvantages. A study in India showed that protection against ultraviolet light, sunburn, and suntan was the most reported short‐term benefits of sunscreen, 17 while a study carried out among the Jordanian population showed that skin irritation and acne were the most reported side effects 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, applying "sun protection" has been used instead of "sunscreen use". Healthcare professionals can also increase the rate of sunscreen use with public awareness and through health platforms (48). Gao et al (2014) observed that 90% of the subjects used sunscreen since they believed that it could prevent sunburn (38,43).…”
Section: 6% False)mentioning
confidence: 99%